Boundedness of solutions and asymptotic properties of some systems of differential equations - Gorodetskii, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish conditions under which solutions of some systems of differential equations are bounded and study their asymptotic properties.